Pengaruh Citra Merek (Brand Image), Wom (Word Of Mouth) Dan Persepsi Harga Terhadap Minat Beli Smarthphone Pada Mahasiswa Universitas 17 Agustus 1945 Surabaya - Valeria N.K Wati; Hotman Panjaitan (Universitas 45 Surabaya, 2023)
This study aims to determine the effect of Brand Image, WOM (Word Of Mouth) and Price Perception on Purchase Intention. The population in this study were all students of the University of 17 August 1945 Surabaya, totalling 12,819. The sampling technique used purposive sampling with a sample size of 100 respondents obtained from calculations using the slovin formula. Sample collection using questionnaires conducted online and offline with the help of google form.Based on the results of the study, multiple linear regression analysis was obtained as follows Y = 15.871 + -0.029 (X1) + 0.245 (X2) + 0.413 (X3) The results of the t test hypothesis (partial test) state that the Brand Image variable (X1) has no effect on the Purchase Interest variable (Y), WOM (Word Of Mouth) (X2), Price Perception (X3) partially affects the Purchase Interest variable (Y). The results of the F test (simultaneous test) state that the Brand Image variable (X1), WOM (Word Of Mouth) (X2), Price Perception (X3) simultaneously affect the Purchase Intention variable (Y).